2016
DOI: 10.1007/978-981-10-1498-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs: New Players in Cancers

Abstract: The world of noncoding RNAs (ncRNAs) has gained widespread attention in recent years due to their novel and crucial potency of biological regulation. Noncoding RNAs play essential regulatory roles in a broad range of developmental processes and diseases, notably human cancers. Regulatory ncRNAs represent multiple levels of structurally and functionally distinct RNAs, including the best-known microRNAs (miRNAs), the complicated long ncRNAs (lncRNAs), and the newly identified circular RNAs (circRNAs). However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 349 publications
(239 reference statements)
0
47
0
Order By: Relevance
“…Recently, increasing evidence confirms that long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) have been identified as important regulators in a variety of cancers including HCC (Bartel, 2004;Li and Chang, 2014;Wang et al, 2017). Abnormal expression of lncRNA plays a key role in cancer progression and carcinogenesis through a variety of mechanisms (Chen et al, 2016). LINC00346 is located on chromosome 13q34, with a total length of 6322bp, and is up-regulated and has oncogenic effects in non-small cell lung cancer and bladder cancer (Ye et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidence confirms that long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) have been identified as important regulators in a variety of cancers including HCC (Bartel, 2004;Li and Chang, 2014;Wang et al, 2017). Abnormal expression of lncRNA plays a key role in cancer progression and carcinogenesis through a variety of mechanisms (Chen et al, 2016). LINC00346 is located on chromosome 13q34, with a total length of 6322bp, and is up-regulated and has oncogenic effects in non-small cell lung cancer and bladder cancer (Ye et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) are two kinds of non-coding RNAs, which are not able to encode any protein [4]. The existing researches have showed that the abnormally expressed lncRNAs, miRNAs and proteins regulate the EMT progression of HCC cells via their interactions [57].…”
Section: Introductionmentioning
confidence: 99%
“…Noncoding RNAs (ncRNAs) are defined as RNAs possessing little capability of protein‐coding. They function as promising regulators of epigenetic, transcriptional, and posttranscriptional gene expression . Generally, based on the lengths, ncRNAs are categorized into small ncRNAs (shorter than 200 nucleotides, like microRNAs [miRNAs], small interfering RNAs [siRNAs], and transfer RNAs [tRNAs]) and long ncRNAs (lncRNAs) (longer than 200 nucleotides, like lincRNAs and macroRNAs) .…”
Section: Introductionmentioning
confidence: 99%